Jenis-Jenis Kayu dan Perhitungan Volume Bahan Pembuatan Kapal Nelayan Tradisional di Kabupaten Bolaang Mongondow Utara - Nani, Andra; Salam, Aziz; Baruadi, Alfi Sahri (The NIKe Journal, 2023)
This research aims to find out the types of wood used to make traditional boats and to find out the estimated need for wood used to make traditional fishing boats in Bolangitang II Village, West Bolangitang District, North Bolaang Mongondow Regency. The research was carried out in March-June 2021. Data was collected using a survey method carried out in two ways, namely interviews and direct sample measurements. Data regarding types of wood were analyzed descriptively and calculated the boat beam volume, board volume, board volume coefficient, Mahera length coefficient, and Mahera diameter coefficient. The results of the research show that the katinting boats in Bolangitang II Village are made of wood, the wood material is selected from trees of good quality based on the experience of the boatman. To calculate the estimated need for wood for making a boat, namely the volume of boards and the length and diameter of the mahera, you can use the board volume coefficient (Cp), Mahera length coefficient (Cpm) and Mahera diameter coefficient (Cdm). In this study, the values of Cp = 0.0592, Cpm = 0.7050, and Cdm = 0.7444 were obtained.